Cybersecurity 4.0: safeguarding trust and production in the digital food industry era - Alqudhaibi, Adel; Krishna, Ashish; Jagtap, Sandeep; Williams, Nikki; Afy-Shararah, Mohamed; Salonitis, Konstantinos (Springer, 2024)
The food industry is vital manufacturing sector globally, with an ever-increasing reliance on digitalisation and technology-driven processes. However, this advancement introduces inherent cyberattack risks, encompassing data breaches and system disruptions, which can severely impact production and disrupt the entire food chain. Consequently, cyber threats can evoke fear and mistrust among consumers, potentially tarnishing a company's brand. This paper presents a comprehensive research methodology, including an extensive literature review and a detailed survey, aimed at assessing the current state of cybersecurity within the food industry. The problem at hand is the industry's apparent lack of robust cybersecurity measures to protect against the growing threat landscape, which this research aims to address. Our findings reveal a clear gap in cybersecurity preparedness within the food industry, with potential vulnerabilities that could be exploited by cyber adversaries. In response, we propose a specialised security framework designed to mitigate these risks. The framework is built upon a thorough analysis of the industry's existing cybersecurity posture and the identification of both current and emerging cyber threats. The contribution of this research relies in the development of a security framework that strengthens the industry's cyber defenses, thereby enhancing its competitive advantage. The framework emphasizes the importance of continuous employee education and training as a cornerstone for improving the security environment. Enhancing the security environment through ongoing employee education and training is crucial for fostering consumer trust and enabling seamless growth within the industry. By adopting a proactive approach to cybersecurity, the food industry can ensure the sustainability and reliability of its operations in the face of evolving cyber threats.
Keywords: Cybersecurity; Cyberattacks; Food sector; Supply chain; Digitalization; Employee training